A dictionary of the Kedang language : Kedang-Indonesian-English - Samely, U. B.; Barnes, R. H. (Robert Harrison), 1944-; Amuntoda, A. Sio; Apelabi, M. Suda (Handbuch der Orientalistik. Südostasien ;, 2013)
A Dictionary of the Kedang Language presents the first extensive published record of an Austronesian language on the remote Eastern Indonesian island of Lembata, a region on the boundary between Austronesian and Papuan languages.